Religion as brand image in local beauty brand advertising / Mohd Fauzi Harun…[et.al] - Harun, Mohd Fauzi; Husain, Halim; Albakry, Nur Safinas; Nik Abdullah, Nik Narimah; Ramli, Zahara; Johari, Mohd Hisham; Wan Muhammad Zulkifli, Wan Nurul Izzati (Academy of Contemporary Islamic Studies (ACIS), 2019)
The cut-throat competitive market environment has made the advertising field very experimental and hence advertisers are adopting different measures to attract the attention of their target customers. Many companies try to convince Muslim consumers that their products are Shariah-compliant. In persuading whether or not their claim has any truth value, it is perhaps inevitable in today’s capitalist world that religion come to be commodified. This advertising conflict practice is important to study especially in evaluate the social interaction in the formation of meanings for individuals or even society. The presentation of religious symbol or iconography basically been utilized by all the religions of the world so that each religion could identify each other. In advertisement, these symbols can be communicate through object, picture, sign, word, or even complex artistic forms and gestures used as a kind of key to convey religious concepts, association of certain ideas or events. The study is conducted to examine the influence of religion on local beauty brand and discover the Islamic commodification of brand image on advertisement by Muslim & Non-Muslim. The „signs‟ used is more than selling purpose but implied with hidden messages and influences that later affects actions and thoughts of the viewer as well as what they do automatically are often governed by a complex set of cultural messages and conventions. 9 respondents from different background were selected from a convenience sampling method in semi-structured interview to provide more opportunities to glean insights about the topic. Culture has been perceived as a high influential aspect in advertising strategy especially in term of visual and text used. Cultural values of different background of viewers also governs ideas in giving interpretation of what was served to them in the advertisement. Even though they do understand it is a matter of brand image towards targeted consumer which is Malay-Muslim, some advertisement have the potential of misleading messages which can be considered as a harmful approach to the collective behaviours of the society. This so called “normal‟ advertisement is a tactful manner that consumer goes psychologically under the pressure of advertising persuasiveness rather than to sell the products as the basic aim of advertising.